1997
DOI: 10.1002/(sici)1098-2795(199701)46:1<39::aid-mrd7>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the mouse CSF-1 gene

Abstract: Research in our laboratory is aimed at understanding the cellular and molecular mechanisms that govern colony stimulating factor‐1 (CSF‐1) gene expression. Our hypothesis is that a basal set of trans‐acting factors is bound to the CSF‐1 gene during fibroblast proliferation, resulting in constitutive CSF‐1 gene expression. Modulation of CSF‐1 gene transcription by growth‐arrest (decrease) or stimulation of growth‐arrested fibroblasts (re‐initiate) is mediated by changes in the basal set of factors bound and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Our study is aimed at understanding the mechanism of CSF-1 gene regulation in osteoblast cells. Previous studies have shown that interleukin-1 and tumor necrosis factor are potent stimulators of CSF-1 gene expression (49). CSF-1 is released from osteoblasts constitutively and in response to parathyroid hormone and parathyroid hormonerelated protein (50).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is aimed at understanding the mechanism of CSF-1 gene regulation in osteoblast cells. Previous studies have shown that interleukin-1 and tumor necrosis factor are potent stimulators of CSF-1 gene expression (49). CSF-1 is released from osteoblasts constitutively and in response to parathyroid hormone and parathyroid hormonerelated protein (50).…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory stimuli, such as LPS, IFN-␥, and IL-1␤ induce MCSF production by monocytes, endothelial cells, fibroblasts, T cells, and polymorphonuclear leukocytes (13)(14)(15). PMA up-regulates mammalian MCSF expression in macrophages (16), B lymphocytes (17), T lymphocytes (18), and malignant cells (19).…”
Section: Two Macrophage Colony-stimulating Factor Genes Exist In Fishmentioning
confidence: 99%
“…It acts as a transcriptional repressor of genes that enhance proliferation, i.e. early growth response (Madden et al, 1991), granulocyte colony-stimulating factor (Harrington et al, 1993), insulin-like growth factor II (Drummond et al, 1992), insulin-like growth factor I receptor (Werner et al, 1993), platelet-derived growth factor A chain (Gashler et al, 1992;Wang et al, 1992), transforming growth factor b-1 (Dey et al, 1994), bcl-2 and c-myc (Hewitt et al, 1995). In addition, it can also enhance transcription of growth inhibitory genes, i.e.…”
Section: Wt-1mentioning
confidence: 99%